IgG4‐related disease—experience of 100 consecutive cases from a specialist centre. Issue 5 (24th January 2017) - Bateman, Adrian C; Culver, Emma L
Abstract : Aims: To describe the features of 100 consecutive cases referred to a single UK institution in which a diagnosis of IgG4‐related disease (IgG4‐RD) was under consideration. Methods and results: The histological features were reviewed by a single histopathologist, and cases were categorized according to the 2012 Boston criteria: Category 1—histologically highly suggestive of IgG4‐RD; Category 2—probable histopathological features of IgG4‐RD; and Category 3—insufficient histopathological evidence of IgG4‐RD. A 'global assessment' was performed with the available clinical information: Assessment group 1—'definite/very likely IgG4‐RD'; Assessment group 2—'possible IgG4‐RD'; Assessment group 3—'not IgG4‐RD'; and Assessment group 4—insufficient information. The mean IgG4+ plasma cell count and IgG4+/IgG+ ratio were highest in Category 1 [134/high‐power field (HPF); 57%] and Assessment group 1 (113/HPF; 52%), and lowest in Category 3 (11/HPF; 18%) and Assessment group 3 (43/HPF; 31%) (Category comparison of IgG4+ count and ratio, both P < 0.001; Assessment group comparison of IgG4+ count, P < 0.0002; and Assessment group comparison of ratio, P = 0.04). A non‐IgG4‐RD diagnosis was rare in Category 1 (7%) but common in Category 2 (60%) and Category 3 (47%). Stromal reactions to neoplasia and chronic oral ulceration were simulants of IgG4‐RD. Conclusions: The Boston criteria are linked to the likelihood of IgG4‐RD. Other conditions may show some histological features of IgG4‐RD. The likelihood of IgG4‐RD is much greater when the histological features reach the threshold for Category 1 than when they reach the thresholds for Categories 2 and 3. Despite the utility of the Boston criteria, this study highlights the crucial importance of careful clinicopathological correlation when a diagnosis of IgG4‐RD is under consideration.